EXPLORATION OF THE BIOACTIVE POTENTIAL OF RHIZOPHORACEAE MANGROVE PLANTS: IMPLICATIONS IN THE FIELD OF FISHERIES - Mulyani, Yuniar; Mulyani, Yeni; Aisyah, Aisyah (Universitas Mataram, 2025)
Mangrove forests, as coastal ecosystems rich in biodiversity, play an important role in ecology and the fisheries sector. Mangroves not only function as coastal protectors and habitats for aquatic organisms but also produce bioactive compounds that have potential as antibacterial, antioxidant, antifungal, and antiviral agents. Research on mangrove plants from the Rhizophoraceae family, such as Bruguiera, Kandelia, Ceriops, and Rhizophora, has shown that compounds like flavonoids, tannins, alkaloids, and saponins have significant biological activities. Flavonoids act as antimicrobials, while tannins inhibit bacterial growth by precipitating proteins. Alkaloids disrupt bacterial cell walls and have potential in combating cancer cells. Studies also reveal significant antioxidant activity, with some mangrove extracts showing great potential in combating free radicals. Moreover, these compounds offer potential in reducing reliance on synthetic antibiotics for the treatment of cultured fish diseases and provide opportunities for the development of natural-based health products. This review aims to integrate recent findings on the bioactivity of mangrove plants and propose innovative applications of bioactive compounds in fisheries and conservation with a focus on ecosystem sustainability and optimal use of natural resources.